Memmler's human body in health and disease. - Cohen, Barbara J.; Taylor, Jason J. (Philadelphia : Lippincott Williams & Wilkins, 2005)
"A low-level introductory text on basic human anatomy and physiology with disease coverage for HP students in programs including medical assisting, surg tech, massage, certified nursing assistant, respiratory tech, and the like. Organized by body system; includes BOB CD with Stedman's pronunciations, selected figures (from text) in DHA engine, and student review questions"--Provided by publisher.
Organization of the human body -- Chemistry, matter, and life -- Cells and their functions -- Tissues, glands, and membranes -- Disease and disease-producing organisms -- The skin in health and disease -- The skeleton: bones and joints -- The muscular system -- The nervous system: the spinal cord and spinal nerves -- The nervous system: the brain and cranial nerves -- The sensory system -- The endocrine system: glands and hormones -- The blood -- The heart and heart disease -- Blood vessels and blood circulation -- The lymphatic system and lymphoid tissue -- Body defenses, immunity, and vaccines -- Respiration -- Digestion -- Metabolism, nutrition, and body temperature -- Body fluids -- The urinary system -- The male and female reproductive systems -- Development and birth -- Heredity and hereditary diseases.
Includes index.
System requirements for accompanying CD-ROM: Windows: Windows 2000, Windows NT 4.0, or Windows XP, Pentium II, Internet Explorer 5.5 or higher or Netscape 7.02; Macintosh: Apple Power Macintosh or compatible computer, MAC OS version 9.2 or later, Internet Explorer 5.1 or Netscape 7.01, Microsoft PowerPoint or PowerPoint Viewer.
Keywords: Human physiology; Physiology, Pathological; Human anatomy; Physiology; Anatomy; Pathology